Safety and health management system, safety climate, and accident occurrences in hospitals: The study of needlestick, sharp injuries and recidivism rates - Jafar Akbari; Ahmad Ghadami; Mohammad Reza Taheri; Nasrin Khosravi; Shirin Zamani (Wolters Kluwer Medknow Publications, 2023)
Background: Hospital Safety and Health Management System (HSH-MS) and Hospital Safety Climate (HSC) are the significant elements to develop safe work practices. The current study aimed to examine the dimensions of HSH-MS and HSC and the association with the prevalence of Needlestick and Sharp Injury (NSI) and NSI recidivism. Materials and Methods: A cross-sectional study was conducted among 1070 nurses in Iranian hospitals (89% response rate). Results: More than 54% (n = 579) had sustained at least 1 NSI in the previous year. The NSI recidivism rate was 8.6% and recidivists were more likely to be younger, female, married, with higher Body Mass Index (BMI), and on night shift. Two aspects of HSH-MS including management leadership and employee participation were associated with the incidence of NSIs Odds Ratio (OR): 1.91 and 95% Confidence Interval (CI): 0.69-1.21; OR: 1.29 and 95% CI: 0.92-1.82) and NSI recidivism rate (OR: 1.98 and 95% CI: 0.55-1.74; OR: 1.12 and 95% CI: 0.83-1.49). Furthermore, three dimensions of HSC comprising management support (OR: 1.02 and 95% CI: 0.93-1.11 for NSIs; OR: 1.21 and 95% CI: 0.77-1.22 for NSI recidivism), absence of job hindrances (OR: 1.06 and 95% CI: 0.98-1.16 for NSIs; OR: 1.11 and 95% CI: 0.96-1.30 for NSI recidivism) and cleanliness/orderliness (OR: 1.07 and 95% CI: 0.98-1.08 for NSIs; OR: 0.84 and 95% CI: 0.87-0.97 for NSI recidivism) were correlated with reduced NSIs risk. Conclusions: This study suggests that HSH-MSs and employees' safety climate are significant factors, which are correlated with not only the prevalence of recurrent NSIs but also the single NSI in hospitals.